2022
DOI: 10.1017/s2040174422000198
|View full text |Cite|
|
Sign up to set email alerts
|

Limosilactobacillus fermentum prevents gut-kidney oxidative damage and the rise in blood pressure in male rat offspring exposed to a maternal high-fat diet

Abstract: Oxidative stress along the gut-kidney axis is a risk factor for developing arterial hypertension in offspring from dams fed a high-fat diet. Considering the antioxidant capacity of probiotic strains, this study evaluated the effects of a daily multistrain formulation with Limosilactobacillus fermentum 139, 263, and 296 on blood pressure (BP), renal function, and oxidative stress and along the gut-kidney axis in male offspring from dams fed a high-fat high-cholesterol (HFHC) diet during pregnancy and lactation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This has been observed in both in vitro and experimental studies, as well as in some clinical trials [ 39 , 40 ]. In the male offspring of female mice fed with a high-fat high-cholesterol diet, the application of fermented Limosilactobacillus fermentum reduced systolic and diastolic blood pressure, and mean blood pressure levels, as well as alleviated renal function damage and oxidative stress along the intestinal renal axis [ 41 ]. Furthermore, functional capacity analysis revealed that Limosilactobacillus fermentum was significantly and positively associated with KEGG pathways related to flagellar assembly.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in both in vitro and experimental studies, as well as in some clinical trials [ 39 , 40 ]. In the male offspring of female mice fed with a high-fat high-cholesterol diet, the application of fermented Limosilactobacillus fermentum reduced systolic and diastolic blood pressure, and mean blood pressure levels, as well as alleviated renal function damage and oxidative stress along the intestinal renal axis [ 41 ]. Furthermore, functional capacity analysis revealed that Limosilactobacillus fermentum was significantly and positively associated with KEGG pathways related to flagellar assembly.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, kidney development is roughly from mid-pregnancy to mid-lactation. Table 1 summarizes preclinical studies recording offsprings’ renal outcomes in which maternal high-fat diets were applied during gestation and lactation [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Although maternal obesity is frequently studied using rodents on high-fat diets, it is clear that the programming effects of maternal obesity and high fat consumption on offspring outcomes are different [ 76 ].…”
Section: Renal Programming: the Impact Of A Maternal High-fat Dietmentioning
confidence: 99%
“…Activation of the classic RAAS through high fat intake can lead to vasoconstriction, oxidative stress, and inflammation, resulting in kidney disease [ 103 , 104 ]. Hypertension in maternal-high-fat-diet-primed offspring coincides with aberrant activation of the classic RAAS, represented by increases in the renal protein level of AT1R and mRNA expression of Agt and Ace [ 64 ].…”
Section: Mechanisms Linking Maternal High-fat Diets To Renal Programmingmentioning
confidence: 99%
See 2 more Smart Citations